Efeito do AW-HRL-c como estratégia terapêutica antiparasitária e imunomoduladora na esquistossomose mansônica experimental - Guimaraes, Victor Hugo (Universidade Federal de São Carlos, 2026)
Schistosomiasis mansoni remains a relevant public health problem in Brazil, where approximately 1.5 million people live in endemic areas. Although praziquantel (PZQ) is the reference treatment and exhibits efficacy and safety, the reliance on a single anthelmintic and reports of reduced susceptibility in some contexts described in the literature reinforce the need for therapeutic alternatives. In this study, silver tungstate anchored with curcumin (AW-HRL-C) was evaluated in a murine model of experimental schistosomiasis mansoni through parasitological and immunological analyses. Parasitic load, systemic and local leukocyte profiles, plasma cytokines by CBA, and peritoneal cavity lavage cytokines by ELISA were examined. A trend toward a reduction in egg deposition and a decrease in worm recovery were observed in animals treated with AW-HRL-C compared to the infected and untreated control, in addition to changes in the leukocyte profile, which were more evident in the peritoneal environment. In plasma, only IL-10 showed consistent detection, with a reduction in the treated groups. In the peritoneal cavity lavage, the treated groups exhibited an IL-4 profile between the infected/untreated control and the uninfected control, with no significant differences for TNF-α, IL-6, IFN-γ, and IL-10. Taken together, these findings suggest that AW-HRL-C possesses antiparasitic and immunomodulatory potential in experimental schistosomiasis mansoni. However, further studies on dose-response, in vivo toxicity, histopathology, and mechanism of action are required to define its safety and efficacy at different stages of the parasite.
Effect of AW-HRL-c as an antiparasitic and immunomodulatory therapeutic strategy in experimental schistosomiasis mansoni
Keywords: esquistossomose; Schistosoma mansoni; curcumina; imunomodulação; tungstato de prata; CIENCIAS BIOLOGICAS::PARASITOLOGIA; 3. Saúde e Bem-Estar